Review of Tunnel Fire Damage Assessment Methods and Techniques. Issue 5 (May 2021) - Hua, Nan; Elhami-Khorasani, Negar; Tessari, Anthony
Major tunnel fires can have catastrophic consequences, including loss of life, property damage, and long-term service disruptions. The rapid rise of gas temperature in excess of 1, 000°C (1, 832°F) inside a confined tunnel space as well as long fire duration because of limited emergency responder access necessitate special design considerations when evaluating the structural response to fire. Although tunnel stability is not challenged in most cases, severe damage to the concrete lining is observed after major fire events. This paper provides a detailed review of assessment methodologies and techniques of fire damage in concrete tunnel linings, including guidance on the determination of fire scenarios, concrete spalling, and tunnel safety from existing codes and guidelines, experiments, and numerical models. Based on the review, the need to develop relevant guidelines is emphasized, the knowledge gaps in the existing research are identified, and future research directions are proposed.